2014
DOI: 10.1007/s00402-014-2075-8
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive plate osteosynthesis using 3D Printing for shaft fractures of clavicles: technical note

Abstract: This article describes a minimally invasive plate osteosynthesis technique for midshaft fractures of clavicles using intramedullary indirect reduction and prebent plates with 3D printing models. This technique allows for easy reduction of fractures with accurate prebent plates and minimal soft tissue injury around the fracture site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…In preoperative planning, 3D-printed biomodels have been beneficial in orbital and mandibular reconstruction in maxillofacial surgery (21, 3741); craniofacial, skull base, and cervical spine reconstruction in neurosurgery (35); prefabrication of bony fixation plates and planning excision of bony lesions in orthopedic surgery (42, 43); mapping complex congenital heart defects and tracheobronchial variation in cardiothoracic surgery and cardiac transplantation (26, 4452) (Figure 2); endovascular repair of abdominal aortic aneurysm and aortic dissection in vascular surgery (5355); partial nephrectomy for renal tumors in urology (56); osteoplastic flap reconstruction of frontal sinus defects in ear, nose, and throat surgery (57, 58); and hepatectomy and liver transplantation in general surgery (5961). …”
Section: D Printing In Medicinementioning
confidence: 99%
“…In preoperative planning, 3D-printed biomodels have been beneficial in orbital and mandibular reconstruction in maxillofacial surgery (21, 3741); craniofacial, skull base, and cervical spine reconstruction in neurosurgery (35); prefabrication of bony fixation plates and planning excision of bony lesions in orthopedic surgery (42, 43); mapping complex congenital heart defects and tracheobronchial variation in cardiothoracic surgery and cardiac transplantation (26, 4452) (Figure 2); endovascular repair of abdominal aortic aneurysm and aortic dissection in vascular surgery (5355); partial nephrectomy for renal tumors in urology (56); osteoplastic flap reconstruction of frontal sinus defects in ear, nose, and throat surgery (57, 58); and hepatectomy and liver transplantation in general surgery (5961). …”
Section: D Printing In Medicinementioning
confidence: 99%
“…A key advantage offered by additive manufacture is the ability to create personalized treatments and devices at a relatively low cost compared with traditional manufacturing processes. The use of 3D printing for planning of complex surgery is one aspect, Jeong et al 4 reported using this technique to perform accurate pre‐bending of osteosynthesis plates to allow minimally invasive fracture repair. The other main application is the creation of custom devices, which can reduce operative time and improve outcomes 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…These may be related to extensive exposure of the fracture site and stripping of peripheral soft tissues. 2,8,9,28,34 Intramedullary nailing may minimize soft tissue injuries during fracture reduction. However, problems, such as malunion or nonunion, migration or nail breakages, difficulty in controlling clavicular rotation, and low fixation quality of the nail, are still concerns.…”
mentioning
confidence: 99%